The incubation advantage : leveraging business model innovation and entrepreneurial ecosystems for start-up growth - Braun, Sjard (2023)
Guided by the pursuit of advancing economic growth, this study explores how incubators can assist growth-oriented start-ups with business model innovation and foster entrepreneurial ecosystems. By addressing these previously neglected catalysts of start-up growth, this research contributes to enhancing the effectiveness of incubator programs. The study, employing a qualitative research methodology, draws on semi-structured interviews with start-ups enrolled in an industry-agnostic incubator from central Finland and industry experts from Finland and Spain. The research explores key drivers of business model innovation, examines the associated characteristics and challenges, and identifies mechanisms that incubators can employ to foster such innovation. Additionally, the study sheds light on pertinent actors within entrepreneurial ecosystems, potential partners for start-ups, the learning opportunities entrepreneurs derive from these ecosystems, and the collaborations that incubators should establish to facilitate start-up growth. The findings underscore the instrumental role of incubators in facilitating business model innovation activity among start-ups and emphasize the position of incubators as vital linkages within entrepreneurial ecosystems. In addition, the study shows how entrepreneurial ecosystems can equip start-ups with the expertise and resources needed to internationalize to promote start-up growth further. The investigation offers implications for policymakers and practitioners seeking to encourage entrepreneurship and drive economic growth. The study's insights can serve as guiding principles for designing and implementing more effective incubation programs.